Sustaining population levels and understanding the implications of housing density - A review of the approach in Belmont, Western Australia - Brunner, Julie; Hammah, Juliette (Routledge, 2013)
Providing opportunities to house-predicted population growth is often considered to be simply a matter of increasing housing densities to provide for the construction of more dwellings. National policies aimed at accounting for this growth prescribe approaches and set targets that may result in outcomes contrary to those desired by or beneficial to the local community. Increases in housing densities applied in isolation and through a blanket approach can actually generate a decrease in population, a significant change in population characteristics and social circumstances and make housing less affordable. This is demonstrated through a longitudinal study of the strategic approach to housing provision in the City of Belmont, Western Australia.